Study of the Influence of the Molecular Weight of the Polymer Used as a Coating on Magnetite Nanoparticles - Chapa, Christian (Springer Nature, 2018)
Designing coated magnetic nanoparticles for nanomedicine applications, such as magnetic resonance imaging contrast enhancement, hyperthermia, and drug-delivery, has been in the focus of scientific interest for the last decade. Biocompatible polymers are used as nanoparticles coating for its physical and chemical properties that are very useful for biomedical applications. The aim of this contribution was to prepare the magnetite nanoparticles stabilized with poly (ethylene glycol) (PEG) and poly (ethylene glycol) methyl ether (mePEG) to elucidate the influence of the molecular weight on the corresponding amount of coating. The X-ray diffraction studies determined inverse spinel structure of magnetite nanoparticles, and field–emission scanning electron microscopy indicated the formation of quasi-spherical nanostructures with the final average particle size of 88–136 nm depending on the type of polymer coating. The bonding status of different polymers on the magnetite nanoparticles was confirmed by the Fourier transform infrared spectroscopy. According to the thermogravimetric analysis polymer amount in nanocomposites is related to molecular weight in the PEG-modified MNPs. The results of this study indicate the possibility of controlling the properties of theranostics nanomaterials, starting from the molecular weight of the polymer used as a coating.